Troponin I Cutoff for Non-ST-Segment Elevation Myocardial Infarction in Sepsis - Tsai, Meng-Ko; Lai, Chao-Hung; Hung, Chia-Lien; Wu, Keng-Yi (Mediators of Inflammation, 2022)
The diagnostic value and optimal cutoff level of cardiac troponin I in patients with sepsis have not been studied. In this single hospital retrospective study, we assessed the optimal cutoff value of troponin I for diagnosing non-ST-segment elevation myocardial infarction (NSTEMI) with type 1 myocardial infarction (MI) in patients with sepsis who had undergone a percutaneous coronary intervention from 2009 to 2019. In total, 5,341 patients (excluding patients with chronic kidney disease) were included, of whom 277 had sepsis or septic shock. Of the 123 patients with non-ST-segment elevation acute coronary syndrome (NSTE-ACS) and sepsis, 77 (62.6%) were diagnosed with NSTEMI with type 1 MI. The receiver-operating characteristic curve showed an area under the curve (AUC) of 0.705 for diagnosis of NSTEMI with type 1 MI with a troponin I cutoff of >300 ng/L (sensitivity: 68.4%, specificity: 70.2%, Youden index: 0.386). Multiple linear regression showed no significant predictors of NSTEMI with type 1 MI. Troponin level and the Global Registry of Acute Coronary Events (GRACE) scores were correlated (R2=0.0625, p=0.032) and showed comparable predictive value for 6-month mortality (AUC: 0.637 and 0.611, respectively, p=0.7651). The optimal troponin I cutoff to effectively diagnose NSTEMI with type 1 MI in patients with sepsis was 300 ng/L.